2016
DOI: 10.1080/07448481.2016.1213732
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect as a moderator of the relationship between hookup motives and hookup consequences

Abstract: Objective The current study examined the extent to which negative affect moderates the relationships between distinct hookup motives and hookup consequences. Participants Data were collected from 271 heavy drinking undergraduate college students. Methods Students from three U.S. universities completed online surveys assessing hooking up related motives, behaviors, and consequences. Results The results showed that conformity motives to hookup and negative affect predicted hookup consequences. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…It is also consistent with other studies (Pedersen et al, 2017), in which participants, through their narratives, share that having wild experiences to recount to friends is important to them. In addition, the fact that all young women in M2 recall engaging in sexual-affective relationships that they did not enjoy or choosing partners who they did not like is also in accordance with studies (Montes et al, 2016(Montes et al, , 2017 showing that students experiencing peer pressure to engage in casual relationships seem more susceptible to adverse outcomes related to hooking up.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also consistent with other studies (Pedersen et al, 2017), in which participants, through their narratives, share that having wild experiences to recount to friends is important to them. In addition, the fact that all young women in M2 recall engaging in sexual-affective relationships that they did not enjoy or choosing partners who they did not like is also in accordance with studies (Montes et al, 2016(Montes et al, , 2017 showing that students experiencing peer pressure to engage in casual relationships seem more susceptible to adverse outcomes related to hooking up.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, gratification and pleasure in these cases seems to be related to the perceived social status. In addition, several studies show that students who felt pressured by their peers to engage in casual relationships seemed more susceptible to adverse outcomes related to hooking up, as well as were those hooking up with multiple partners (Montes et al, 2016(Montes et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Whether students prefer relief from negative affect at the cost of experiencing negative hookup consequences is an interesting question that future research is needed to address. Although conformity hookup motives were not found to be predictive of negative hookup consequences in the current study, conformity hookup motives have been found to be positively associated with negative hookup consequences (Montes et al, 2016). Taken together, these findings suggest that negatively reinforcing hookup motives (i.e., coping and conformity) may be important predictors of negative hookup consequences.…”
Section: Discussioncontrasting
confidence: 81%
“…Some of the consequences that students experienced as a result of hooking up included: regret, embarrassment, disappointment, sexual dissatisfaction, and the contracting of a sexually transmitted infection (STI; Bachtel, 2013; Napper et al, 2015; Tomsich, Schaible, Marie Rennison, & Gover, 2013). To better understand the conditions under which negative hookup outcomes are experienced, researchers have examined predictors and moderators of negative hookup consequences, including attitudes, motives, negative affect, and attachment style (e.g., Lewis et al, 2012; Montes, Napper, Froidevaux, Kenney, & LaBrie, 2016; Owen et al, 2014). An important predictor which has received scant research attention in the hookup literature is injunctive norms.…”
mentioning
confidence: 99%
“…Relationship-focused motives such as entering a CSRE with the goal of forming a romantic relationship were associated with more negative emotional reactions in studies of both Canadian and American college students (Gusarova et al, 2012;Montes et al, 2016). Individuals with avoidant motives such as coping or conformity also tended to experience more negative subjective emotional reactions (Montes et al, 2017(Montes et al, , 2016, and individuals with non-autonomous motives tended to have lower self-esteem (Vrangalova, 2015a).…”
Section: Psychosocial Constructsmentioning
confidence: 99%